2014
DOI: 10.2494/photopolymer.27.399
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Radicals for Gene Transfection by Discharge Plasma Irradiation

Abstract: The authors parametrically investigated gene transfection process with a micro capillary discharge. Several factors and the time scale at which they became effective were studied. The conclusion is that half of transfections occur during plasma irradiation and the other half occur after plasma irradiation is stopped. As the electric field and current become zero after plasma irradiation is terminated, we conclude that during that period radical species are necessary for the transfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 4 publications
2
39
0
Order By: Relevance
“…Transfection achieved using viruses is often called transduction. Novel approaches using non-thermal plasma have recently been developed (Jinno et al 2014;Sasaki et al 2014).…”
Section: Gene Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection achieved using viruses is often called transduction. Novel approaches using non-thermal plasma have recently been developed (Jinno et al 2014;Sasaki et al 2014).…”
Section: Gene Transfectionmentioning
confidence: 99%
“…40). Jinno et al 2014 investigated the gene transfection process using a micro capillary discharge device (see Fig. 41) and found that half of the transfection process occurred during plasma irradiation and the other half occurred after plasma irradiation stopped.…”
Section: Gene Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma species impacting the membrane come from a low temperature air micro‐plasma generated at atmospheric pressure. This plasma setup has been already used for gene transfection . It can be considered as a pulsed corona discharge generated in ambient air from the tip of an anodic copper tube of 70 μm for outer diameter.…”
Section: Descriptions Of Input Data and Monte Carlo Modelmentioning
confidence: 99%
“…The present Monte Carlo model is aimed to statistically simulate, at a global (or macro) scale, the pore formation during atmospheric pressure plasma interactions with cell membrane. The plasma species interacting with membrane come from a low temperature micro‐plasma generated in air at atmospheric pressure already used for gene transfection . In our preliminary Monte Carlo simulations, a simplified model membrane is assumed as a superposition of four layers involving two internal phospholipid‐like layers surrounded by two external protein‐like layers.…”
Section: Introductionmentioning
confidence: 99%